2018
DOI: 10.1021/acs.biochem.7b01076
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Hsp90-Independent Interaction between Co-Chaperone p23 and Transcription Factor p53

Abstract: Cancer-suppressing transcription factor p53 is regulated by a wide variety of cellular factors, including many chaperones. The DNA-binding domain (DBD) of p53 is known to interact with the chaperone Hsp90, but the role of other members of the chaperone network, including co-chaperones such as p23, is unknown. Using a combination of nuclear magnetic resonance (NMR) titration, isothermal titration calorimetry, fluorescence anisotropy, and native agarose gel electrophoresis, we have identified a direct interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In addition to the central role p23/Sba1 plays in the Hsp90 cycle, p23/Sba1 also exerts Hsp90-independent functions. These include chromatin remodeling, ribosome biogenesis (Echtenkamp et al 2011(Echtenkamp et al , 2016, and Hsp90-independent interaction with tumor-suppressor protein 53 ( p53), which is supposed to compete with its DNA binding (Wu et al 2018).…”
Section: Non-tpr-containing Cochaperonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the central role p23/Sba1 plays in the Hsp90 cycle, p23/Sba1 also exerts Hsp90-independent functions. These include chromatin remodeling, ribosome biogenesis (Echtenkamp et al 2011(Echtenkamp et al , 2016, and Hsp90-independent interaction with tumor-suppressor protein 53 ( p53), which is supposed to compete with its DNA binding (Wu et al 2018).…”
Section: Non-tpr-containing Cochaperonesmentioning
confidence: 99%
“…Sti1/Hop was found to be overexpressed in certain cancers (Chao et al 2013;Carvalho da Fonseca et al 2014) and to promote invasion when present in the extracellular space (Walsh et al 2011). Interestingly, mutated p53 seems to induce the expression of Sti1/Hop (Mattison et al 2017) and p23 was shown to directly bind and modulate p53 in a Hsp90-independent manner (Wu et al 2018). Silencing of Cdc37 destabilized kinases and thus, sensitized cancer cells to Hsp90 inhibition (Smith et al 2009).…”
Section: Hsp90 Cochaperones and Diseasementioning
confidence: 99%
“…We can foresee other consequences of the binding of AIT to p23 because this cochaperone has been shown to bind to the DNA‐binding domain (DBD) of p53, as it is the case for Hsp90 (Wu, Hyun, Martinez‐Yamout, Park, & Dyson, 2018). This raises the intriguing possibility that p23 affects the cancer‐suppressing transcription factor p53 and that AIT modulates this function.…”
Section: Discussionmentioning
confidence: 99%
“…Human Hsp90α, 4,19 p53(88-312), 3,19 p23, 19,20 Hsp70, 21 Hsp40, 22 and HOP 23 were prepared as described previously. The published preparation of 15 N-labeled p53 yields the folded, zinc-bound form.…”
Section: Protein Preparationmentioning
confidence: 99%
“…Native agarose gel electrophoresis was used to investigate protein-protein interactions using published protocols. 19,24 Typically, a 50-100 μM p53 sample was analyzed with binding partners Hsp90 and p23 at concentration ratios ranging from 0:0 to 2:0 or 2.5:0. Zinc binding to apo p53 DBD was analyzed using concentration ratios (zinc sulfate:apo p53 DBD) from 0:0 to 20:0.…”
Section: Nmr Spectroscopy and Gel Electrophoresis Conditionsmentioning
confidence: 99%